Beyond bullet points : using Microsoft Office PowerPoint 2007 to create presentations that inform, motivate, and inspire - Atkinson, Cliff (Redmond, Wash. : Microsoft Press, 2008)
A guide to using Microsoft PowerPoint describes how to use storytelling techniques to create effective business presentations.
Book is accompanied by one CD entitled' Beyond bullet points : using Microsoft Office PowerPoint 2007 to create presentations that inform, motivate, and inspire' bearing the same call number and is available at Bahagian Koleksi Media.
Buku bacaan asas fakulti.
Includes index.
Keywords: Microsoft PowerPoint (Computer file).; Microsoft PowerPoint (Computer software); Business presentations -- Graphic methods -- Computer programs; Multimedia systems in business presentations; Computer graphics; Business -- Computer software